Prospective comparative study between retroperitoneoscopic and hand-assisted laparoscopic approach for radical nephrectomy - Tobias-Machado,Marcos (2009)
OBJECTIVE: No consensus has yet been established regarding the best minimally invasive access for radical ablation of renal tumors. Our objective was to prospectively compare the surgical results and oncologic management of two currently used endoscopic techniques. MATERIAL AND METHODS: Over a four-year period, 50 patients with renal tumors and clinical stage T1b-T2, smaller than 12 cm, underwent a radical nephrectomy at two reference institutions, 25 underwent retroperitoneoscopic radical nephrectomy (RRN) and 25 a hand-assisted laparoscopic radical nephrectomy (HALRN). Mean follow-up of both cohorts was 50 months. Operative parameters and oncological management were compared. RESULTS: The mean operative time was 180 min in RRN and 108 min in HALRN (p < 0.001). The time required to access the renal pedicle in RRN was 30 min. and in HALRN 40 min., Learning curve was shorter in HALRN than RRN. Mean blood loss was 100 mL in RRN and 242 mL in HALRN. Mean incision size for specimen retrieval in RRN was 6.5 cm and in HALRN 7.5 cm. One patient with intra operative occurrence of ascites and subsequent pathological stage pT2N0M0 grade 3 operated via HALRN, had neoplasic implants in the Hand-port incision 3 months after surgery followed by death 4 months after recurrence. One patient, with pathological stage pT3N0M0 grade 3 in RRN had metastasis after 36 months. CONCLUSION: Both, RRN and HALRN techniques are accepted minimally invasive options for endoscopic radical nephrectomy with equivalent long term oncological outcome in the treatment of renal tumors.